Tuberculosis, Anaemia and Erythropoietin: a study evaluating the role of erythropoietin in the pathophysiology of the anaemia of tuberculosis - Ebrahim, Osman (Department of Medicine, 2021)
Although it is more than 100 years since Robert Koch discovered the tubercle bacillus, and more than 40 years since effective chemotherapy became available, tuberculosis remains a major cause of morbidity and mortality in the world to-day. A major contributor to the morbidity is anaemia. This anaemia falls under the classification of anaemia of chronic disorders, the pathogenesis of which has not been fully elucidated. With the advent of recombinant human erythropoietin (Epo ), it has become evident that a blunted Epo response to the anaemia plays a major role. The mechanism (s) involved still have to be elucidated. The aims of, this study were to evaluate serum Epo levels and iron parameters in anaemic patients with active pulmonary tuberculosis (PTB) and investigate the effect of tumour necrosis factor alpha (TNFa) produced by activated macrophages in PTB patients on Epo production in vitro. Furthermore, the mechanism involved in Epo gene expression was investigated. Haematological and biochemical parameters (including serum iron and Epo) were I studied prospectively in four groups each of 1 O subjects. Group I comprised newly diagnosed non-pregnant individuals with pulmonary tuberculosis (PTB), haemoglobin below 110 g/L, and having no apparent dissemination or other I associated systemic illnesses. Group II were age and sex matched PTB patients with haemoglobin levels greater than 130 g/L. Group III ·consisted of otherwise healthy ' people with demonstrated absolute iron deficiency anaemia with haemoglobin corresponding to those in Group I. Group IV consisted of 10 healthy non-anaemic volunteers. For matching degrees of anaemia, the serum Epo was significantly lower in Group I than in Group III patients. In PTB, therefore, the Epo response to anaemia is attenuated. With anti-tuberculous therapy there was a significant increase in the Hb and serum iron levels in the Group I patients which correlated with a fall in the levels of the inflammatory marker C-reactive protein (CRP). This argues for the degree of inflammation being casually related to the anaemia. To further investigate the effect of inflammation on Epo production, blood samples were collected. from individuals in Groups I, II and III and the peripheral blood mononuclear cells (I>BMC) were assayed for the cytokine TNFa. The incubation of supernatant fractions (SNF) of the anaemic PTB group with HepG2 cells resulted in a marked inhibition of Epo production by these cells. Dose response studies showed that increasing concentration of SNF resulted in a progressive reduction in Epo production, which could be reversed by the presence of anti-TNFa antibodies in the: medium. Thus TNFa is capable of inhibiting Epo production and may play a role in the blunted Epo response to anaemia seen in patients with PTB. In order to characterize the mechanisms involved in oxygen sensing, the murine Epo gene was studied to define the sequences within the enhancer involved in oxygen sensing and Epo gene expression. To this end, transfection experiments of deleted, mutated and re-iterated enhancer sequences located 3' to the poly (A) signal sequence were carried out in HepG2 cells and in the non-Epo producing lung fibroblastoid cell line a23. Transcription factor binding to the enhancer was investigated by DNA I footprint analysis and revealed that at least three sites within a 96 nucleotide sequence 0f the Epo enhancer were critical. Oxygen regulated operation was dependent on sites ' ' within the first 25 nucleotides. In both HepG2 and a23 cell lines the same two critical sites in the 5' region of the enhancer were necessary for function. Sequences located 3' to this region modulated enhancer function but did not themselves convey oxygen regulated operation. This study has contributed to the understanding of the pathophysiology of the I anaemia of tuberculosis in that in this disease, TNFa released from activated macrophages was capable of inhibiting Epo production in vitro. This may explain the attenuated Epo response to anaemia in PTB patients. Furthermore, three critical sites on the Epo enhancer were shown to be essential for oxygen sensing and Epo gene expression. It can be postulated, therefore, that TNFa may disrupt the interaction of transcription factors with critical sites of oxygen sensing on the enhancer and prevent the increased production of Epo. Further work is required to clarify this postulate.